(untitled) (2013)
A simple and rapid method is proposed for the removal of chromium based on its adsorption as anion pair with Cetyl Trimethyl Ammonium Bromide (CTABr) on a silica gel column. The surfactant (CTABr) is bonded to chromate by electrostatic force of attraction and the resulting ion-association complex is held on a silica gel column. The resulting solution from the column is analyzed for chromium by the standard diphenyl carbazide spectrophotometric procedure. The method has been applied successfully to study the recovery of chromium in various synthetic mixtures.